Effect of insulin-resistance on circulating and adipose tissue MMP-2 and MMP-9 activity in rats fed a sucrose-rich diet - Miksztowicz, Verónica Julieta (2014)
Background and aim: Adipose tissue produces different metalloproteinases (MMPs), involved in adipogenesis and angiogenesis. Different studies have shown that in obesity the behavior of different MMPs may be altered. However there are scarce data about the effect of insulin-resistance (IR) on MMP-2 and MMP-9 activity in adipose tissue. Our aim was to determine whether sucrose induced IR modifies MMP-2 and MMP-9 behavior in expanded visceral adipose tissue and the contribution of this tissue to circulating activity of these gelatinases. Methods and results: Male Wistar rats were fed with standard diet (Control) or standard diet plus 30% sucrose in the drinking water throughout 12 weeks (SRD). In epididymal adipose tissue vascular density, size and adipocyte density, PPARγ expression and MMP-2 and -9 were measured. Adipose tissue from SRD presented higher adipocyte size (6.32 ± 8.71 vs 4.33 ± 2.17 × 103 μm2, p = 0.001) lower adipocyte density (164 (130–173) vs 190 (170–225) number/mm2, p = 0.046) and lower vascular density (16.2 (12.8–23.5) vs 28.1 (22.3–46.5) blood vessels/mm2, p = 0.002) than Control. MMP-2 and MMP-9 activity was decreased in SRD (1.93 ± 0.7 vs 3.92 ± 0.9 relative units, p = 0.048 and 1.80 ± 0.8 vs 5.13 ± 1.7 relative units, p = 0.004 respectively) in accordance with lower protein expression (0.35 ± 0.20 vs 2.71 ± 0.48 relative units, p = 0.004 and 1.12 ± 0.21 vs 1.52 ± 0.05 relative units, p = 0.036 respectively). There were no differences in PPARγ expression between groups. Conclusion: Insulin resistance induced by SRD decreases MMP-2 and MMP-9 activity in adipose tissue which would not represent an important source for circulating MMP-2 and -9. In this state of IR, PPARγ would not be involved in the negative regulation of adipose tissue gelatinases.